Agricultural trade policies and child nutrition in low- and middle-income countries: a cross-national analysis. - Adjaye-Gbewonyo, Kafui.; Vollmer, Sebastian.; Avendano, Mauricio.; Harttgen, Kenneth. (Tufts University. Tisch Library., 2019)
Background: There has been growing interest in understanding the role of agricultural trade policies in diet and nutrition. This cross-country study examines associations between government policies on agricultural trade prices and child nutrition outcomes, particularly undernutrition.; Keywords: Nutrition status, Trade, Agriculture, Policy, Food prices, Nominal rate of assistance, Liberalization.; Springer Open.